Biocomputing 2006 2005
DOI: 10.1142/9789812701626_0033
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Regulated Networks During Hiv-1 Latency and Reactivation

Abstract: Human immunodeficiency virus (HIV) affects millions of people across the globe. Despite the introduction of powerful anti-viral therapies, one factor confounding viral elimination is the ability of HIV to remain latent within the host genome. Here, we perform a network analysis of the viral reactivation process using human gene expression profiles and curated databases of both humanhuman and human-HIV protein interactions. Based on this analysis, we report the identification of active pathways in both the late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Krishnan et al showed altered expression levels of genes encoding components of the proteasome, histone deacetylases, and transcription factors in the chronically infected cell lines ACH-2, J1.1, and U1 compared to the parental uninfected cell lines A3.01, Jurkat, and U937 (56). The same data set was used later on to identify several networks at the latent stage, including an enrichment of proteins associated with HIV-1 replication, apoptosis, and cell growth regulation (58). Since latently infected cells cannot be distinguished from uninfected cells in vivo, only a comparative study of resting memory CD4 ϩ T cells from viremic and aviremic subjects has been done so far (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krishnan et al showed altered expression levels of genes encoding components of the proteasome, histone deacetylases, and transcription factors in the chronically infected cell lines ACH-2, J1.1, and U1 compared to the parental uninfected cell lines A3.01, Jurkat, and U937 (56). The same data set was used later on to identify several networks at the latent stage, including an enrichment of proteins associated with HIV-1 replication, apoptosis, and cell growth regulation (58). Since latently infected cells cannot be distinguished from uninfected cells in vivo, only a comparative study of resting memory CD4 ϩ T cells from viremic and aviremic subjects has been done so far (59).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our microarray study indicated that in latently infected cells, gene programs were modulated in a way that is consistent with cell quiescence, cell survival, transcription silencing, and evasion of the immune system. Since HIV-1 proteins have a profound effect on many host cell functions that are relevant to its life cycle (55,58,(62)(63)(64)(65)(66)(67)(68)(69), it is conceivable that they might also affect cell functions relevant to latency. On the other hand, it is possible to speculate that a subset of CD4 ϩ T cells with a gene expression profile similar to the one emerging from our microarray analysis already preexists in peripheral blood of healthy individuals, so that upon HIV-1 infection, it provides an ideal environment for the establishment of latency.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, co-clustering of RNAi data with protein-protein networks identified HCV-responsive modules in humans, establishing the role of human ESCRT-III complex as an infection-permissive host factor 81 . Other discoveries of omics-derived modules using protein interaction knowledge have spanned a variety of model organisms, including metabolism in yeast 48 , drug response in Mycobacterium tuberculosis 50 , aging in Drosophila 89 , aging 56 and embyogeneisis in C. elegans 34 , and cellular responses to inflammation 87 , HIV infection 61 , or TNF-mediated stress 90 in humans.…”
Section: Identification Of ‘Active Modules’mentioning
confidence: 99%
“…More recently, Calderwood et al (15) empirically constructed a map of physical protein interactions between the EpsteinBarr-Virus and the human host. For HIV, subnetworks of virus-host protein interactions that are expressed at different stages of the infection have been identified (16) along with cofactors that enable HIV and the influenza virus to infect a host cell (17)(18)(19). Furthermore, Dyer et al compared experimentally known interactions of different viruses with the human host (20).…”
mentioning
confidence: 99%